Knowledge, attitude and practice regarding dengue: a case study in Taman Temerloh Jaya, Malaysia - Nasaruddin, Nur Khairunnisa; A. Rahman, Nor Azlina; Mamat, Suhana (LAP Lambert Academic Publishing, 2014)
Dengue is an endemic tropical and subtropical disease caused by dengue virus. It is being transmitted by Aedes mosquito, mostly in urban and semi-urban areas. A cross-sectional study was carried out to assess the knowledge, attitude and practice (KAP) regarding dengue and its prevention among residents in Taman Temerloh Jaya, Malaysia using a structured interviewer-administered questionnaire. The KAP of the participants were described accordingly. The KAP were also analysed in order to find out their associated factors and to see whether there was any relationship between knowledge, attitude and practice regarding dengue and its prevention.